Colombian Oil Energy Security through a Framework of Risks and Vulnerabilities - Grimaldo-Guerrero, John; Rivera-Alvarado, Juan; Acosta-Bustamante, Jainer; Cabeza-Abello, Tulio; Osorio-Tovar, Jose (International Journal of Energy Economics and Policy, 2024)
The dynamics of oil markets are influenced by both international and local contexts, which determine their potential for success and sustainability. This article uses a conceptual methodology to analyze the characteristics that are present in successful energy markets. These characteristics can help identify inhibitors and barriers that may hinder the growth and development of the market. The analytical-propositive methodological design consists of three phases: firstly, a diagnosis is conducted to describe the costs associated with oil production, which will allow for the identification of economic characteristics. Secondly, attributes of the Colombian oil market are identified through a documentary and regulatory analysis. Finally, strategic guidelines are inferred, which can be used as inputs for the formulation of energy policies. The results highlight that sustainable development policies must involve both public and private actors to strengthen decision-making and the quality of processes, thereby providing greater scope.